1990
DOI: 10.1210/jcem-71-2-487
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Synthesis of Inhibin Subunits in Human Decidua*

Abstract: A growing number of studies provided the evidence that human decidua is a pregnancy-related tissue capable of hormone production and metabolism. The aim of the present study was to evaluate the possible presence of inhibin subunits in human decidua. Tissue samples were collected in pregnant women during the first (8 weeks) and second trimester (18 weeks) of gestation and at term (40 weeks). Immunohistochemical data were obtained using affinity purified polyclonal antisera raised in rabbit against porcine alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(36 citation statements)
references
References 21 publications
3
33
0
Order By: Relevance
“…Maternal decidual cells stained with both inhibin a and b B antisera showed a similar localisation. Cells stained with b A subunit were sparse and followed a distribution pattern different from that of cells stained with a or b B antisera (18). This study's data are consistent with other reports showing that high concentrations of inhibins (19,20) and 'total' activin A (23) are present in the amniotic fluid.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Maternal decidual cells stained with both inhibin a and b B antisera showed a similar localisation. Cells stained with b A subunit were sparse and followed a distribution pattern different from that of cells stained with a or b B antisera (18). This study's data are consistent with other reports showing that high concentrations of inhibins (19,20) and 'total' activin A (23) are present in the amniotic fluid.…”
Section: Discussionsupporting
confidence: 89%
“…Messenger RNA for inhibin a subunit has been identified in the syncytiotrophoblast and inhibin/activin b A and b B mRNAs have been identified in both cytotrophoblast and syncytiotrophoblast in the placenta (2). Immunocytochemical staining has also shown the presence of the a subunit, b A subunit and the b B subunit protein in syncytiotrophoblast (16,17) and the decidua (18).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical studies can also be useful, because decidual cells express estrogen receptor and alpha inhibin, markers that are absent in mesotheliomas. [45][46][47] As some early immunohistochemical studies were unable to demonstrate keratin expression in deciduosis, 43 some investigators suggested that immunostaining for this marker could assist in distinguishing deciduoid peritoneal mesothelioma from deciduosis. 1 Subsequent studies, however, demonstrate that both human decidua and extrauterine decidual reactions can be keratin positive and, therefore, keratin immunostaining has no value in discriminating between mesotheliomas with deciduoid features and deciduosis.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, the human trophoblast (2,3), fetal membranes (4) and decidua (5,6) express subunit mRNAs and immunoreactive proteins. Significant amounts of both proteins are secreted into the biological fluids of pregnancy (maternal and cord serum, coelomic and amniotic fluids) (7), and the feto-placental unit is the main source of circulating inhibin A and activin A (8).…”
Section: Introductionmentioning
confidence: 99%